2013
DOI: 10.1038/leu.2013.384
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 is essential for MLL leukemia partially via crosstalk with the MEIS/HOX pathway

Abstract: Mixed lineage leukemia (MLL) fusion proteins directly activate the expression of key downstream genes such as MEIS1, HOXA9 to drive an aggressive form of human leukemia. However, it is still poorly understood what additional transcriptional regulators, independent of the MLL fusion pathway, contribute to the development of MLL leukemia. Here we show that the transcription factor PU.1 is essential for MLL leukemia and is required for the growth of MLL leukemic cells via the promotion of cell-cycle progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 56 publications
1
48
1
Order By: Relevance
“…These studies indicated that the presence of PU.1 activity may be required to favor the growth of myeloid leukemia stem cells. Previous studies have reported that PU.1 demonstrated an essential expression and activated a well-known oncogene MEIS1 pathway in MLL, accompanied by MEIS1 overexpression (16). In addition, the expression of the PU.1 gene and the survival rate appeared to be inversely associated in human AML samples with MLL rearrangement (16).…”
Section: A B a Bmentioning
confidence: 96%
See 4 more Smart Citations
“…These studies indicated that the presence of PU.1 activity may be required to favor the growth of myeloid leukemia stem cells. Previous studies have reported that PU.1 demonstrated an essential expression and activated a well-known oncogene MEIS1 pathway in MLL, accompanied by MEIS1 overexpression (16). In addition, the expression of the PU.1 gene and the survival rate appeared to be inversely associated in human AML samples with MLL rearrangement (16).…”
Section: A B a Bmentioning
confidence: 96%
“…In addition, there is a positive association between the expression of PU.1 and MEIS1 in MLL patients, and the regulation of MEIS1 by PU.1 is central to the pathogenesis of leukemia harboring MLL rearrangements (16). However, the function of PU.1 and its mechanism in non-MLL remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations